Students' problems and behavioral characteristicsin visual art education / Nor Eliza Md Nasir - Md Nasir, Nor Eliza (2013)
Teachers at all grade levels in Malaysian schools face challenges in conducting effective classroom instruction especially in art lessons. Certain strategies such as classroom rules, verbal praise and reprimands, and loss of privileges may not produce the desired outcomes due to student problems in Visual Art classes. This study is concerned with the students' lack of skills and interest in the subject of Visual Art Education for schools in Malaysia. The study took place in an urban school in Selangor. Quantitative and qualitative approaches were used to study the problem; data including the students' skills, interest, background as well as the teachers, school location and the activities in the classroom were collected using questionnaires, interviews, survey and observation. The art students from Form Three Mahir, Four Ceria and Five Ceria were involved in this correlation research. They were sampled from a population of fifteen students and five teachers. These mix methods data collections were used like simple calculations of percentage to determine the students' problems and the effective strategies of dealing with various behavioral situations. Findings from the survey showed the student's involvement in the visual art activities, and appropriate methods to deal with students' inappropriate behavioral situations. The findings may also help the school to assess and study the school program for evaluation. The study may help the researcher, school and university to implement the teaching practice more generalization corporate.